Nuclear receptor-driven immunometabolic crosstalk: immune-centric pharmacology targeting the inflamed nexus - Zhang, Yang; Pei, Zhenzhen; Wen, Zhige; Chen, Yupeng; Wang, Haoshuo; Tan, Weili; Chen, Xin; Liu, Jingbo; Ni, Qing (Frontiers in Cell and Developmental Biology, 2026)
Chronic low-grade inflammation (metaflammation) constitutes a shared pathological nexus in obesity, type 2 diabetes mellitus (T2DM), and non-alcoholic fatty liver disease (NAFLD). While current therapies primarily alleviate metabolic symptoms, they often neglect underlying immune dysregulation orchestrated by nuclear receptors (NRs). This review proposes immune-centric pharmacology, a paradigm directly targeting immunocytes (e.g., macrophages, T cells) through spatiotemporal modulation of NR-mediated immunometabolic crosstalk (e.g., PPARγ/δ, FXR, LXRs) to disrupt inflammation-perpetuating microenvironments. We emphasized NRs as main regulatory factors of immunophenotypic reprogramming, spanning the interactions of fat, liver, and intestinal immunity, and comprehensively summarized the multicellular structure of “inflamed nexus.” We gradually expand our discussion from the following three aspects: immune reprogramming targeting nr by novel biological agents (for example, TREM2 agonists activating PPARγ); advanced transmission systems enable tissue-specific NR regulation.; and the immunomodulatory mechanism of metabolic drugs utilizing the NR-immune axis. Current findings indicate that focused immunomodulation achieves via NR-guided immune-centric pharmacology represents a transformative framework for next-generation metabolic disease management, bridging pharmacological innovation with therapeutic translation.